IMPLEMENTASI NILAI-NILAI PENDIDIKAN KARAKTER MELALUI PEMAHAMAN KAJIAN AL-QUR’AN SURAT LUQMAN AYAT 12-14 (Analisis Deskriptif Kelas 5 DTA Al-Muttaqien Kecamatan Indihiang Kota Tasikmalaya) - Rudi Permadi; Cecep Bahrul Salim (HASBUNA : Jurnal Pendidikan Islam, 2023)
This article discusses the implementation of character education values through understanding the study of the Al-Qur'an Surah Luqman Verses 12-14 in Class 5 of Al-Muttaqien DTA, Indihiang District, Tasikmalaya City. The background of this research is that the situation of students continues to change from time to time along with the development of technology, and often children misuse or take advantage of these developments, as well as poor relationships in society or parental attention at home, giving rise to problems that damage a child's character. In this research, the author made direct observations at the research site, namely DTA Al-Muttaqien, and used other data sources such as tafsir books and other literature books related to this research. The aim of this research is to try to reveal comprehensively about character formation through understanding the study of the Al-Qur'an Surah Luqman verses 12-14. This research methodology uses descriptive methods with a qualitative approach. The research results show that the implementation of character education values through understanding the study of the Al-Qur'an is carried out by instilling the character of gratitude, the character of faith, and the character of filial piety towards parents.